ANALISIS PERLAKUAN AKUNTANSI TERHADAP PEMBIAYAAN KREDIT PEMILIKAN RUMAH IB PADA PT. BANK TABUNGAN NEGARA SYARIAH CABANG SURABAYA - DHARA NOOR FEBRINA, TYSA Noor (Jurnal Akuntansi AKUNESA, 2013)
Islamic banks offer different products with existing products in conventional banksamong others, the most dominating murabahah products among other products.Murabahah is a sale and purchase agreement with a selling price of goods at costplus an agreed profit which the seller must disclose the cost of the item to the buyer.This led the authors to conduct a study of murabahah in BTN Syariah using researchmethods that are explained descriptively. The goal is to know and understand theaccounting treatment of mortgage financing on BTN Syariah. Keywords: Accounting, Islamic banks, Murabahah